Sexual identities of the Malay male in Karim Raslan’s go East and neighbours - Collin Jerome, (Penerbit UKM, 2008)
This paper explores the construction of sexual identities of fictional Malay men in Karim Raslan’s short stories Go East and Neighbours. It begins with a discussion on the complexity and fluidity of male sexuality and how it is mediated through the absence and presence of homosexuality, men’s articulation of sexuality in the public and private realms and men’s fear and insecurity in developing intimate relationship with each other. The paper then presents a brief overview of the depictions of male sexuality in Malaysian literature in English, which is followed by discussions on the absence and presence of homosexuality in Go East and the transgression of male sexuality in Neighbours. The paper concludes that fictional Malay men in Karim Raslan’s short narratives not only transgress the concept of male sexuality but also the socio-cultural and religious norms and boundaries, offering alternative insights into mainstream ideas about sexuality and sexual identity in the contemporary Malaysian society.